What aspects of historical understanding feature in the analysis of moving-image sources in the history classroom?. Issue 2 (20th October 2020) - Cutajar, Alexander
Abstract : page_195 other This paper reflects on aspects of historical understanding developed in a classroom in which moving-image sources are analysed. Considered as non-fictional representations of the past, moving-image sources comprised broadcast images of historical events on newsreels, news broadcasts and documentaries. The study, carried out in a Maltese state secondary school, involved students (aged 15/16 years) analysing moving images as historical sources in their history lessons. Various aspects of understanding were identified: making connections with media content; using knowledge of one topic to shape another; discussing forms of historical knowledge in relation to each other; connecting with the wider historical picture; and constructing meaning using various language strategies. It is argued that these aspects offer a characterization of historical understanding when analysing broadcast footage of historical events in a constructivist classroom. It is suggested that underlying these aspects was students' prior historical knowledge. I highlight the importance of maximizing on opportunities provided by moving-image sources to support understanding, particularly the co-construction of knowledge.